دراسة مورفومترية على الفاروا Varroa sp. المتطفل على نحلة العسل السورية 'Apis mellifera syriaca' (Latakia University Journal -Biological Sciences Series, 2019)
One hundred and ninety eight samples of honeybee mites, infecting Syrian honeybee 'Apis mellifera syriaca', were from five different locations covering the main beekeeping regions of Syria and analyzed morphometrically in the laboratory of honeybee researches in Faculty of Agriculture, University of Damascus. The measurements taken were the body length and width (Anderson & Trueman 2000). The results were compared with those of V. jacobsoni and V. destructor reported by (Anderson & Trueman 2000) to confirm which species of mite is present on Syrian honeybee. No significant differences were shown between specimens coming from the five different Syrian regions. However, remarkable differences were present between Varroa mites infecting Syrian apiaries and both Varroa species already known (destructor and jacobsoni, Anderson and Trueman 2000). تم دراسة مئة وثمانية وتسعين طفيل فاروا  Varroa sp.متطفلاً على سلالة نحل العسل السورية 'Apis mellifera syriaca' من خمس محافظات سورية، تمثل هذه المحافظات النشاط النحالي الأهم في سورية. درست هذه العينات مورفومترياً في مختبر بحوث نحل العسل في كلية الزراعة بجامعة دمشق عام 2005 ، حيث تم قياس كل من طول جسم الطفيل وعرضه .(Anderson & Trueman 2000) تم مقارنة النتائج مع المعطيات المورفومترية لكلٍ من النوعين العالميين المعروفين لهذا الطفيل  V. destructor و  V. jacobsoni (Anderson & Trueman 2000) وذلك من أجل توصيف وتحديد نوع الفاروا الذي يصيب سلالة نحل العسل السورية. لم تلاحظ خلال التحليل الإحصائي أية فروقات احصائية بين عينات الطفيل الأتية من المحافظات السورية الخمسة مما يثبت أنها تعود لنوع واحد. في حين أن الفروقات كانت معنوية بين كل من العينات المحلية لهذا الطفيل (باعتبارها نوعاً واحداً) وكل من النوعين العالميين الموصوفين مسبقاً.